Analysis of pharmaceutical service improvement based IPA (Importance Performance Analysis) at pharmacy Kimia Farma Ijen, Malang - Nurmawati, Dian; Priyono, Tridoso Sapto Agus; Siswidiasari, Arifani (JURNAL ILMU KEFARMASIAN INDONESIA, 2025)
Pharmaceutical services are direct and responsible services to patients related to pharmacy to achieve real results and improve patients' quality of life. This study aims to analyze the improvement of pharmaceutical services at the Kimia Farma 36 Ijen Pharmacy using the IPA (Importance Performance Analysis) method. The method used is descriptive research with a quantitative approach through questionnaire instruments. The SERVQUAL (Service Quality) model was used to measure the pharmaceutical service questionnaire. Sampling by the Accidental sampling technique. Questionnaires were distributed to patients or families of patients who redeem prescriptions at the Pharmacy in February 2023. The questionnaire refers to the research of Parasuraman, A., Zeithaml, V. A., & Berry adapted to the research context in the pharmacy. The dimensions are empathy, reliability, responsiveness, assurance, and tangibility, which are divided into importance and performance. The IPA method will analyze performance as the X axis and Importance as the Y. The results show that the service aspects require urgent improvement to improve service quality and patient satisfaction. Aspects that need to be improved include product completeness, the physical appearance of the pharmacy building, cleanliness, comfort, and neatness of the pharmacy, as well as the appearance and service of pharmacy officers. Overall, the results of this analysis provide clear guidance on the priorities for improvements that need to be made at Pharmacy Kimia Farma 36 Ijen.